Tightly linked morpholino-nucleoside chimeras: new, compact cationic oligonucleotide analogues. Issue 40 (29th September 2021) - Debreczeni, Nóra; Bege, Miklós; Herczeg, Mihály; Bereczki, Ilona; Batta, Gyula; Herczegh, Pál; Borbás, Anikó
Abstract : The synthesis of oligonucleotide analogues consisting of morpholino and a ribo- or deoxyribonucleoside in which the 5'-amino group of the nucleoside unit provides the nitrogen to the morpholine ring is described. Abstract : The polyanionic phosphodiester backbone of nucleic acids contributes to high nuclease sensitivity and low cellular uptake and is therefore a major obstacle to the biological application of native oligonucleotides. Backbone modifications, particularly charge alterations is a proven strategy to provide artificial oligonucleotides with improved properties. Here, we describe the synthesis of a new type of oligonucleotide analogues consisting of a morpholino and a ribo- or deoxyribonucleoside in which the 5′-amino group of the nucleoside unit provides the nitrogen of the morpholine ring. The synthetic protocol is compatible with trityl and dimethoxytrityl protecting groups and azido functionality, and was extended to the synthesis of higher oligomers. The chimeras are positively charged in aqueous medium, due to the N -alkylated tertiary amine structure of the morpholino unit.